¿Negar o reescribir la Hispanidad? Los nacionalismos subestatales ibéricos y América Latina, 1898-1936 - Núñez Seixas, Xosé M. (El Colegio de México, A.C., 2017)
A good part of the historiographic discussion on the process of nation-building in Spain in the 19th Century has revolved around the question of weak nationalization. However, the fact that Spain had an overseas empire until 1898 has played a secondary role in this debate. From a perspective that emphasizes the transnational character of all nationalisms, this article concretely approaches the interaction between the empire and the nation-building project in Spain in the first half of the 20th Century. To what point did the colonial question in the Caribbean and the Philippines influence the development of the territorial debate between centralization and decentralization in Spain? To what point did emergent regionalisms and substate nationalisms in Spain look to present or former colonies, what did they learn from these experiences and what relationship did they seek to maintain with these territories?